Parental identity formation in mothers is linked to borderline and depressive symptoms: A person-centered analyses - Piotrowski, Konrad (Frontiers in Psychology, 2023)
The formation of a stable parental identity is an important developmental task which parents face. Difficulties in this process can significantly decrease the quality of life and hinder the fulfillment of the parental role. The present study analyzed whether parental identity status, based on the three identity processes from the Meeus-Crocetti model, is related to the severity of borderline and depressive symptoms. Four hundred and fifty-nine mothers aged 18–40 (M = 32.41, SD = 5.09) participated in the cross-sectional study. The results of the cluster analysis revealed the existence of five different parental identity statuses: Achievement, Foreclosure, Searching moratorium, Diffussion, and Moratorium. Significant differences were also observed between parents with different statuses in terms of borderline and depressive symptoms. The study confirmed predictions that mental health difficulties among parents co-occur with low identification with parenthood.